PENGARUH TINGKAT KECUKUPAN MODAL TERHADAP PROFITABILITAS DENGAN RISIKO KREDIT SEBAGAI VARIABEL PEMODERASI - Dhian Andanarini Minar Savitri (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
This study analyzed the influence of bank capital adequacy level to profitability by using credit risk as moderating variable. The data used in this study is conventional banking listed on the IDX period 2011- 2014.The results of this study indicate that the capital adequacy does not affect the profitability, credit risk negatively affect profitability and credit risk can not moderate the influence of capital adequacy rate on bank profitability in Indonesia.